2020
DOI: 10.1128/mbio.00060-20
|View full text |Cite
|
Sign up to set email alerts
|

Host Mucin Is Exploited by Pseudomonas aeruginosa To Provide Monosaccharides Required for a Successful Infection

Abstract: One of the primary functions of the mucosal barrier, found lining epithelial cells, is to serve as a first-line of defense against microbial pathogens. The major structural components of mucus are heavily glycosylated proteins called mucins. Mucins are key components of the innate immune system as they aid in the clearance of pathogens and can decrease pathogen virulence. It has also been recently reported that individual mucins and derived glycans can attenuate the virulence of the human pathogen Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…74,75 Similarly, mucins in the lung and oral cavity, from where bacteria migrate to the lower respiratory tract, 2 inhibit biofilm formation and downregulate toxins and other virulence factors of pathogenic taxa, such as Pseudomonas aeruginosa, preventing their outgrowth and dominance and thereby promoting community diversity. [76][77][78] These protective effects may be subverted, as P aeruginosa can utilize MUC1 for adherence 79 and reside in the mucus to evade exposure to antibiotics, particularly with mucus hypersecretion such as in cystic fibrosis. 80,81 Many bacteria in the GI and respiratory tracts utilize the mucous barrier as a carbon source and are highly adapted to this microenvironment.…”
Section: Microb Iome-mucous Memb R Ane Inter Ac Ti On Smentioning
confidence: 99%
“…74,75 Similarly, mucins in the lung and oral cavity, from where bacteria migrate to the lower respiratory tract, 2 inhibit biofilm formation and downregulate toxins and other virulence factors of pathogenic taxa, such as Pseudomonas aeruginosa, preventing their outgrowth and dominance and thereby promoting community diversity. [76][77][78] These protective effects may be subverted, as P aeruginosa can utilize MUC1 for adherence 79 and reside in the mucus to evade exposure to antibiotics, particularly with mucus hypersecretion such as in cystic fibrosis. 80,81 Many bacteria in the GI and respiratory tracts utilize the mucous barrier as a carbon source and are highly adapted to this microenvironment.…”
Section: Microb Iome-mucous Memb R Ane Inter Ac Ti On Smentioning
confidence: 99%
“…Furthermore, the C. elegans gut environment filters the larger bacterial pool found in natural feeding substrates, leading to the assembly of a core microbiota [31,32]. Such environmental filtering can occur via behavioral food avoidance [33], ingestion rates [34,35], and host mucins [36], among other factors [7,26]. Recent reports have suggested that the worm's innate immunity [37,38] and microbe-microbe interactions [39] play a dominant role in the C. elegans microbiota assembly, but an experimental comparison of the many forces in play is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The mucin concentration of CF sputum ranges from 16-30 mg/mL (1). In the lung, mucin is a source of nutrients for inhabiting microbes (2, 87, 88) and also is involved in microbial adhesion (87), aggregation (89, 90) and dispersion (83).…”
Section: Resultsmentioning
confidence: 99%
“…25,108 The altered biophysical properties of pulmonary mucus in CF contributes to the establishment of chronic infections by pathogens, including P. aeruginosa. [109][110][111] Due to its importance in CF pathogenesis, inclusion of mucin in ASM is critical to fully replicating the in vivo nutritional 26,112,113 and structural 112,[114][115][116] CF pulmonary environment. 13,116,117 However, despite the limitations associated with altered physical and chemical properties of the mucins associated with the purification process and inclusion of a number of mucin-bound impurities [118][119][120] , the most economical choice is commercial porcine gastric mucin (PGM), which is often used as a component of ASM without further purification.…”
Section: Commercial Porcine Gastric Mucin (Pgm) Contains Contaminants Which Affectmentioning
confidence: 99%